Whose Life Counts: Biopolitics and the "Bright Line" of Chloropicrin Mitigation in California's Strawberry Industry. (May 2016) - Guthman, Julie; Brown, Sandy
In the context of the mandated phaseout of methyl bromide, California's strawberry industry has increased its use of chloropicrin, another soil fumigant that has long been on the market. However, due to its 2010 designation as a toxic air contaminant, the US Environmental Protection Agency and California's Department of Pesticide Regulation have developed enhanced application protocols to mitigate exposures of the chemical to bystanders, nearby residents, and farmworkers. The central feature of these mitigation technologies are enhanced buffer zones between treated fields and nearby buildings. Not only do buffer zones inherently privilege neighbors over farmworkers, but the determinations of the size of these buffer zones are also based on acceptable threshold levels and probabilities that allow significant exposures to those they are designed to protect. Moreover, these protocols require human monitors to detect sensory irritation. While the science and technology studies literature is highly useful for understanding the inextricability of science and politics in developing protective measures and is attentive to what counts as data in setting acceptable thresholds, it tends to overlook that social sorting is intrinsic to such regulation. We thus turn to Foucault's biopolitics to make sense of regulations that are designed to protect but inherently allow some to become ill. Doing so illuminates how determinations of the bright line are at once technical–political as well as implicit decisions about whose bodies count.